Políticas migratorias, participación y construcción política de la migración en España - Oso, Laura; López-Sala, Ana; Muñoz-Comet, Jacobo (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2021)
This article offers a state of the art of research on migration policies, participation and the political construction of immigration in Spain. It starts with an overview of migration policy, addressing the impact of the 2008 economic crisis on the configuration of the political agenda. Secondly, it addresses the political participation of immigrants in Spain and their role as “new” voters. Finally, the appearance of the extreme right political party VOX has shifted the classic debates on the attitudes of the population towards immigration and built a new anti-immigration discourse. The article argues that academic interest and scientific production have been modulated in line with the various phases of Spain’s configuration as a country of immigration. The text ends with some reflections on the impact of the COVID-19 crisis, which has opened up a period of major challenge and uncertainty.